A cellulosic liquid crystal pool for cellulose nanocrystals: Structure and molecular dynamics at high shear rates. (November 2015) - Echeverria, Coro; Almeida, Pedro L.; Feio, Gabriel; Figueirinhas, João L.; Godinho, Maria H.
Abstract : Graphical abstract: Highlights: Above a critical CNC concentration (2 wt.% < CNC wt.% < 5 wt.%) the cholesteric phase of HPC/H2 O solution is strongly affected. XRD and spectroscopy measurements indicate that CNC affect the cholesteric phase of LC-HPC solution. Rheo-NMR study and dynamic oscillatory measurements demonstrate that CNCs restricts the mobility of LC-HPC chains. The presence of CNC delays the recovery of the cholesteric structure. Abstract: Cellulose and its derivatives, such as hydroxypropylcellulose (HPC) have been studied for a long time but they are still not well understood particularly in liquid crystalline solutions. These systems can be at the origin of networks with properties similar to liquid crystalline (LC) elastomers. The films produced from LC solutions can be manipulated by the action of moisture allowing for instance the development of a soft motor (Geng et al., 2013) driven by humidity. Cellulose nanocrystals (CNC), which combine cellulose properties with the specific characteristics of nanoscale materials, have been mainly studied for their potential as a reinforcing agent. Suspensions of CNC can also self-order originating a liquid–crystalline chiral nematic phases. Considering the liquid crystalline features that both LC-HPC and CNC can acquire, we prepared LC-HPC/CNC solutions with different CNC contents (1, 2 and 5 wt.%). The effect of the CNC into the LC-HPC matrix was determined by coupling rheology and NMR spectroscopy – Rheo-NMR a technique tailored to analyse orientational order in sheared systems.